Spontaneous Rapid Resolution of Acute Subdural Hematoma: Revelation in the Era of Modern Science - Vemula, Ramesh Chandra; Prasad, BCM; Banavath, Hanuma Naik; Gokanapudi, Sreeram; Reddy, Kalakoti Chandra Sekhar (Indian Journal of Neurotrauma, 2022)
Acute subdural hematoma (SDH) with mass effect and midline shift is an indication for emergency surgery in neurotrauma. A very few case reports were present in the literature showing rapid resolution of acute SDH with improvement in clinical condition of the patient within hours after trauma. In this article, we presented a case of acute SDH that showed almost disappearance of hematoma within 5 hours after trauma.
Keywords: head injury; acute SDH rapid resolution; miracle in the science; revelation in modern science